DEVELOPMENT OF ON MACHINE MEASUREMENT OF CNC MILLING MACHINE AXIS STRAIGHTNESS USING PROXIMITY SENSOR - Raditya Nugraha, Yoga
Straightness is an important parameter in a machine tool because it can affect the accuracy and precision of the products produced. A commonly used measuring instrument for measuring straightness on the axis of machine tools is a laser interferometer, although it has high accuracy laser interferometer has several disadvantages, expensive equipment costs, long setup and measurement times which have an impact on the productivity of machine tools. This final project aims to develop a straightness measurement method on the axis of motion of CNC milling machines using proximity sensors as an alternative to laser interferometers. This method is designed to be able to reduce production downtime by permanently installing the proximity sensor inside the CNC machine. The method used in this research involves setting up the measurement setup, calibrating the proximity sensor, and comparing the straightness measurement results between the proximity sensor and laser interferometer. The results show that the proximity sensor provides a lower output compared to the output of the laser interferometer. The largest difference in value or error produced by the proximity sensor is 14.2 microns at the -260 mm position. In addition, it was found that the error generated by the proximity sensor increases significantly when the given deviation gets larger and decreases again when the given deviation gets smaller. The main assumption of this inaccuracy is the difference in quality between the two tools, the laser interferometer has a much higher price compared to the proximity sensor. In conclusion, proximity sensors can be used as a more economical alternative for straightness measurement on CNC machines, although it has some limitations in terms of accuracy. The development of better calibration methods is needed to improve the accuracy of proximity sensors in various measurement conditions.